Metoda Warstwy Elastooptycznej w Zastosowaniu do Modelowego Badania Przestrzennych Zagadnień Kontaktowych - Doroszkiewicz, R.S.; Lietz, J.; Michalski, B. (Engineering Transactions, 1967)
This is a description of model tests of three-dimensional contact problems by the method of photoelastic layer. The advantages of this method for the study of contact problems are discussed. The experimental technique is described and illustrated by an example concerning the investigation of the stress concentration in a compressed cylinder with a notch. The method described has been applied to the investigation of stress distribution in. the rollers and the rings of a roller bearing under various loads and various forms of the corrected rollers. This investigation enables some general conclusions to be drawn, concerning the influence on cooperation between the contacting elements of the bearing of the type and the magnitude of the correction.